Immunology of the bovine uterus and immunological strategies to resolve endometritis - DHALIWAL, G S; SIDHU, S S (The Indian Journal of Animal Reproduction, 2023)
Endometritis in breeding cattle· occurs during the postpartum period, and is mostly associated with ascending infection involving Arcanobacter pyogenes together with Gram negative anaerobes. Part of the uterine defence mechanisms against bacterial invasion is provided by uterine polymorphonuclear leukocytes (PMNs), whose phagocytic activity depends on bacterial opsonisation by humoral antibodies. The leukocyte count in the uterine lumen is relatively high during the met-oestrus period compared to other phases of the oestrus cycle. Humoral immune response in the bovine reproductive tract is stimulated following local antigen exposure, and the response is site dependent; lgG predominates in the uterus while IgA in the vagina. A part of IgG 1 is synthesised locally in the bovine endometrium while the remaining IgG 1 and whole of the lgG2 in the uterine lumen is derived from the uterine blood circulation. Intrauterine infusion of immunomodulators, such as E. coli lipopolysaccharides (LPS) or oyster glycogen, in healthy cows and those with endometritis, induces leukocytosis within the uterine lumen; leukocyte count is relatively high during dioestrus but their functional activity is not affected by the stage of the oestrous cycle. Uterine luminal immunosuppressant proteins elevate under progesterone dominance. which inhibit lymphocyte proliferation, thereby making the uterus more susceptible to infections. Exact mechanisms involved in the increased susceptibility of the uterus to infections during the luteal phase of the oestrous cycle are still not clear. E. coli lipopolysaccharides (LPS) when administered intrauterine at a dosage of 100 mg, are not absorbed by the healthy endometrium. and do not alter the oestrous cycle length. It is not known whether this dose of LPS will be absorbed from the inflamed uterus of naturally occurring cases of endometritis, and will cause systemic illness.